ANALYSIS OF THE CULTIVATION OF PANCASILA STUDENT PROFILE VALUES TO BUILD STUDENT CHARACTER IN YPK ERMASU MERAUKE ELEMENTARY SCHOOL - My Ismail; Rudolfus Ruma Bay (Universitas Labuhanbatu, 2024)
AbstractThe Pancasila Student Profile is one of the programmes integrated in the independent learning curriculum initiated by the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia. This programme aims to integrate the ideology of Pancasila as part of the character strengthening curriculum for students so that national insight and the values contained in Pancasila can be adopted by students in their daily lives. Thus, students as the next generation of the nation can have a better attitude and insight into nationalism than the previous generation. The method used in this research is descriptive with a qualitative approach. The results showed that the pancasila student profile programme at SD YPK Ermasu has so far been going well and in a conducive atmosphere. Conditions that must be maintained for the sustainability of the implementation of the Pancasila learner profile programme. Thus, the character of students becomes stronger with the support of their knowledge and understanding of the state ideology, namely Pancasila.Keywords: Value Embedding; Pancasila Learner Profile; Student CharacterAbstrak Profil Pelajar Pancasila merupakan salah satu program yang terintegrasi dalam kurikulum merdeka belajar yang diinisiasi oleh Kementerian Pendidikan, Kebudayaan, Riset dan Teknologi Republik Indonesia. Program ini memiliki tujuan untuk mengintegrasikan ideologi pancasila sebagai bagian dari kurikulum penguatan karakter bagi para pelajar agar wawasan kebangsaan dan nilai-nilai yang terkandung dalam pancasila itu dapat diadopsi oleh pelajar dalam kehidupannya sehari-hari. Sehingga, para pelajar sebagai generasi penerus bangsa dapat memiliki sikap dan wawasan kebangsaan yang lebih baik ketimbang generasi sebelumnya. Metode yang digunakan dalam riset ini adalah deskriptif dengan pendekatan kualitatif. Hasil penelitian menunjukkan bahwa program profil pelajar pancasila yang ada di SD YPK Ermasu sejauh ini berlangsung secara baik dan dalam suasana yang kondusif. Kondisi yang wajib untuk dipertahankan demi terwujudnya keberlanjutan dari pelaksanaan program profil pelajar pancasila. Sehingga, karakter peserta didik menjadi lebih kuat dengan dukungan dari pengetahuan dan pemahamannya terhadap ideologi negara yakni Pancasila.Kata Kunci: Penanaman Nilai; Profil Pelajar Pancasila; Karakter Siswa